Liinc em Revista Vol . 8, n. 1 (2012) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Liinc em Revista Vol . 8, n. 1 (2012)Link de acesso ao númerohttp://revista.ibict.br/liinc/index.php/liinc/issue/view/39